The Critical Research Dimensions of Ghalib’s Poetry by Muhammad Ali Siddique - Dr. Muhammad Farid Ahmed; Dr. samia Komal (Zaban-o-Adab, 2024)
Dr. Muhammad Ali Siddiqi is a renowned critic of progessive movement. He has presented different and unique aspects of Mirza Ghalib’s literary work. He has tried his best to prove that Ghalib is the poet of past and present. He has compared Mirza Ghalib with Sir Syed Ahmed Khan, Iqbal, Meer Taqi Meer, Yas Yagana Changezi, Faiz and other well versed poets. Siddiqi presents Mirza Ghalib as a thinker and philosopher. Besides this, he has presented unique aspects of Mirza Ghalib’s artistic approach related to his poetry. This article also shows Muhammad Ali Siddiqi’s way of research and unqiue critical approach towards the topics being presented by him.